Characterization of essential oil from Ocimum gratissimum leaves: Antibacterial and mode of action against selected gastroenteritis pathogens. (May 2018) - Chimnoi, Nitirat; Reuk-ngam, Nanthawan; Chuysinuan, Piyachat; Khlaychan, Panita; Khunnawutmanotham, Nisachon; Chokchaichamnankit, Daranee; Thamniyom, Wassapol; Klayraung, Srikanjana; Mahidol, Chulabhorn; Techasakul, Supanna
Abstract: Essential oil of fresh leaves of Ocimum gratissimum (OGEO) was water-steam distilled and analyzed by GC-MS. Thirty-seven compounds were identified, with eugenol (55.6%) as the major component followed by cis -ocimene (13.9%), γ-muurolene (11.6%), ( Z, E )-α-farnesene (5.6%), α- trans -bergamotene (4.1%), and β-caryophyllene (2.7%). Antimicrobial activity of OGEO was tested against four gastroenteritis pathogens ( Staphylococcus aureus, Escherichia coli, Salmonella Typhimurium, and Shigella flexneri ). OGEO exhibited antibacterial effect, with MICs of 1–2 mg ml −1, against the tested species. OGEO also displayed rapid killing effect within 5 s at four times of MIC against both E. coli and S. Typhimurium. Various assays were performed to investigate the mode of action of the oil. OGEO increased the permeability of microbial cell membrane as evidenced by LIVE/DEAD Bac Light assay. Analyses of the release of absorbing materials at 260 nm, protein leakage, SDS-PAGE, and SEM strongly suggested the disruptive action of the oil on the cytoplasmic membrane of the tested microorganisms. Results revealed that the antibacterial property of OGEO could be due to membrane disruption. Graphical abstract: Highlights: Essential oil of fresh leaves of Ocimum gratissimum (OGEO) was analyzed by GC-MS. Antimicrobial activity of OGEO was tested against four gastroenteritis pathogens. Various assays were performed to investigate the mode of action of the oil. Results showed that antibacterial property could be due to membrane disruption.